Assessment of multiple subjects' synergetic governance in vocational education - Wu, Min; Sarker, Md Nazirul Islam (Frontiers in Psychology, 2022)
Synergetic governance is a practical approach to ensure quality in the teaching-learning process at multi-dimensional perspectives. This study intends to explore the potential of a synergetic governance approach in the vocational education system. A systematic literature review has been done by applying the PRISMA approach. The last 21 years' literature has been analyzed, and a synergetic governance model has been developed. This study reveals that the synergetic governance of education deals with integrating all available resources to enhance development by meeting the demands of market, society, and nation as a new paradigm. An effective vocational education system requires the participation of all related stakeholders in the governance system. This study has developed an “intervention-approach-synergy-integration” mechanism to show how the education elements are connected to each other. The study reveals that the major synergetic elements are openness, equilibrium, dynamism and cooperation. To ensure synergetic governance, these elements should be integrated with an educational institution, market, public, society, state and private organization. It argues that the synergetic governance of these related components can reduce the demand and supply gap of quality vocational graduates in the industry – academy sectors. This study recommends incorporating multi-subjects' synergetic governance to expedite the marketable quality of vocational education.